A21: Physical Activity in Children with Juvenile Idiopathic Arthritis (JIA): The LEAP (Linking Exercise, Activity, and Pathophysiology in Childhood Arthritis) Study. Issue 11 (March 2014) - Tucker, Lori B.; McKay, Heather A.; Ward, Leanne M.; Houghton, Kristin M.; Rosenberg, Alan M.; Feldman, Debbie Ehrmann; Oen, Kiem; Roth, Johannes; Stringer, Elizabeth; Baxter‐Jones, Adam; Duffy, Ciarán M.; ,
Abstract : Background/Purpose: Although children with JIA have lower fitness levels than healthy peers, little is known about their level of habitual physical activity. The LEAP study is a prospective longitudinal multicentre study of children and teens with JIA, aimed at describing the trajectory of physical activity (PA) in JIA, and its relationship to disease factors, inflammation, quality of life, bone health and muscle function. We report PA levels of children with JIA in early and late disease at study entry. Methods: We enrolled patients with JIA (aged 8–16 y) at 12 pediatric rheumatology centres in Canada as either an inception cohort (early disease; within 6 mos of diagnosis) or an established disease cohort (late disease; > 2yr after diagnosis). We assessed PA with a validated Physical Activity Questionnaire for children (PAQ‐C, age 8–13 y) or teens (PAQ‐A, age 14–16 y). This 7‐day recall self‐report tool has scores from 0 (no PA)‐ 5(high PA). Participants record weekly PA across a wide range of activities and sports. Patients completed a pain scale (VAS 0–100), the Childhood Health Assessment Questionnaire (CHAQ), and Juvenile Arthritis Quality of life Questionnaire (JAQQ). Examining physicians recorded physician global assessment of disease activity (PGA;VAS 0–100) and active joint count. We used univariate and multivariate regression (controlled for gender) to examine relationships between disease and patient factors and PAQ score at study entry. We used PAQ standard population normative values to compare to subjects (female 2.69, SD 0.62; male 3.0 SD 0.72). Results: We included the first 189 patients enrolled (126 F, 63 M, med age 13 y) from March 2012–November 2013. The early cohort included 81 patients (enrolled median 2.4 mo after diagnosis) and the late cohort included 108 patients (enrolled median 4.8 yr after diagnosis). Active arthritis was found in 88 patients, with a mean of 5.5 active joints (range 1–56). PGA was a mean of 13.45 (range 0–74). Overall mean PAQ score for the JIA patients was 2.55 (SD 0.73, range 1–4). Table 1 describes PAQ scores by sex, disease cohort, and presence of active arthritis. When controlled for sex, PAQ scores were significantly different between new onset and late disease, and between patients with active arthritis compared with no active arthritis. Univariate analyses revealed that higher PAQ score were associated with lower pain (p = 0.02), lower CHAQ score (p < 0.0001), higher JAQQ score (p = 0.0001), lower active joints (p = 0.002) and low PGA (p = 0.003). Multivariate analysis confirmed these associations, with R 2 = 0.25, p = 0.000 (girls), R 2 = 0.17, p = 0.01 (boys). Conclusion: Children with JIA report significantly lower levels of PA than healthy peers; this was evident in girls, patients with active arthritis, and in early disease. Disease activity, pain, self reported quality of life and functional status may play a role in moderating PA in JIA.